Neonaucline, a new indole alkaloid from the leaves of Ochreinauclea maingayii (Hook. f.) Ridsd. (Rubiaceae) - Awang, Khalijah; Mukhtar, Mat Ropi; Osman, Norfaizah; Hazni, Hazrina; Qureshi, Ahmad Kaleem; A. Hadi, A. Hamid; Zaima, Kazuma; Morita, Hiroshi; Litaudon, Marc (MDPI, 2012)
A new indole alkaloid; neonaucline (1), along with six known compounds-Cadamine (2), naucledine (3), harmane, benzamide, cinnamide and blumenol A-were isolated from the leaves of Ochreinauclea maingayii (Rubiaceae). In addition to that of compound 1, (13)C-NMR data of cadamine (2) and naucledine (3) were also reported. Structural elucidations of these alkaloids were performed using spectroscopic methods especially 1D- and 2D-NMR, IR, UV and LCMS-IT-TOF. The excellent vasorelaxant activity on isolated rat aorta was observed for the alkaloids 1-3 after injection of each sample at 1 × 10-5 M.